Dampak Penggunaan Metode Ceramah terhadap Minat Belajar Mahasiswa Program Studi Pendidikan Agama Kristen IAKN Palangka Raya Angkatan 2023 - Lelo Lelo (Sukacita : Jurnal Pendidikan Iman Kristen, 2026)
This study was motivated by the dominant use of the lecture method in higher education learning processes, including in the Christian Religious Education Study Program at IAKN Palangka Raya. The lecture method is considered effective in delivering material systematically and efficiently; however, it is often associated with low student participation in learning activities. Therefore, this study aimed to describe and analyze the impact of the lecture method on the learning interest of students in the Christian Religious Education Study Program of IAKN Palangka Raya, Class of 2023. This research employed a qualitative approach using a phenomenological method. The participants were students of the Christian Religious Education Study Program, selected through purposive sampling based on their experiences in attending classes that predominantly used the lecture method. Data were collected through observation, in-depth interviews, and documentation, and were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings revealed that the lecture method has both positive and negative impacts on students’ learning interest. The positive impacts include facilitating students’ understanding of learning materials, providing a more structured delivery of content, and improving instructional time efficiency. However, the excessive use of the lecture method tends to make students less active, easily bored, less attentive during lectures, and less involved in the learning process. The implications of this study indicate that the lecture method remains relevant in higher education; nevertheless, it should be combined with more interactive learning methods, such as discussions, question-and-answer sessions, and presentations, in order to enhance students’ learning interest and participation in the learning process.